2015
DOI: 10.1080/21645515.2015.1030550
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the 13-valent pneumococcal conjugate vaccine compared to the 23-valent pneumococcal polysaccharide vaccine in elderly Japanese adults

Abstract: sive pneumococcal disease; LLOQ, lower limit of quantitation; OPA, opsonophagocytic activity; PCV13, 13-valent pneumococcal conjugate vaccine; PPSV23, 23-valent pneumococcal polysaccharide vaccineStreptococcus pneumoniae is a major cause of severe disease worldwide, particularly in the elderly population. Due to increasing life expectancy in Japan and elsewhere, an effective vaccine which offers the possibility of prolonged protection is required. Protein conjugated pneumococcal vaccines, which have the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…Although a 44% reduction of IPD incidence caused by serotype 3 was reported in the UK among individuals who were aged 65 years or older after the introduction of PCV13 for children, a herd immunity effect against serotype 3 is unclear worldwide [15, 16]. In addition, the immunogenicity of PCV13 against serotype 3 remains controversial in children and was reported to be lower than that of PCV13 serotypes other than serotype 3 in the elderly [1720]. …”
Section: Discussionmentioning
confidence: 99%
“…Although a 44% reduction of IPD incidence caused by serotype 3 was reported in the UK among individuals who were aged 65 years or older after the introduction of PCV13 for children, a herd immunity effect against serotype 3 is unclear worldwide [15, 16]. In addition, the immunogenicity of PCV13 against serotype 3 remains controversial in children and was reported to be lower than that of PCV13 serotypes other than serotype 3 in the elderly [1720]. …”
Section: Discussionmentioning
confidence: 99%
“…All pneumonia patients were hospitalized and none had been vaccinated with PPSV23. Shiramoto et al reported that the immunogenicity of PCV13 and PPSV23, measured as opsonophagocytic activity titer, for serotype 3 were both lower than that for the other serotypes, suggesting lower vaccination efficacy [12]. Another study reported that the effectiveness of the PCV13 vaccine for serotype 3 was not significant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal conjugate vaccine can elicit interaction between T‐helper lymphocytes and B lymphocytes, and induce strong immune responses and immunological memory. PCV13 can reportedly induce higher levels of antibody in elderly people than PPSV23 60,64 . Jackson et al 65 reported that in a randomized double‐blind study involving 936 adults aged ≥ 70 years, the opsonophagocytic activity titers were significantly greater in a PCV13 inoculation group than in a PPSV23 group for 10 of the 12 serotypes common to both vaccines and serotype 6A, which is unique to PCV13.…”
Section: Pneumococcal Vaccinementioning
confidence: 99%
“…PCV13 can reportedly induce higher levels of antibody in elderly people than PPSV23. 60,64 Jackson et al 65 reported that in a randomized double-blind study involving 936 adults aged ≥ 70 years, the opsonophagocytic activity titers were significantly greater in a PCV13 inoculation group than in a PPSV23 group for 10 of the 12 serotypes common to both vaccines and serotype 6A, which is unique to PCV13. Opsonophagocytic activity responses after a follow-on dose of PCV13 a year later demonstrated that a prior dose of PPSV23, but not PCV13, diminished the response to a subsequent administration of PCV13, which indicates better immunogenicity of PCV13.…”
Section: Immunogenicity and Persistencementioning
confidence: 99%